Fall Management: Evaluation of Fall Events in an Inpatient Care Facility - Gurguri, Arberesha (European Scientific Journal, ESJ, 2025)
Introduction: Falls pose a significant risk to older people in nursing facilities. They can lead to serious health consequences, prolonged stays, and impaired quality of life. A systematic evaluation of falls can help identify causes and improve prevention strategies. Objective: The aim of this retrospective study was to analyze falls in a nursing facility over a three-year period. Methods: 290 documented falls were descriptively analyzed between 1 January 2021 and 31 December 2023. Results: The mean age of patients who experienced a fall was 81.26 years. A fall incidence of 5.21 falls per 1,000 patient cases was determined for the survey period. 142 males (48.96%) and 148 females (51.03%) fell. Most falls (68%) occurred in the patient room, particularly between 6:00 a.m. and 8:00 a.m., 4:00 p.m. and 6:00 p.m., while using the toilet, and while walking without assistive devices. The most frequently documented injuries were abrasions (n=45), 15.51%, and bruises. Significant risk factors identified included limited mobility, the use of assistive devices, unsuitable footwear, and a lack of accessibility. Conclusions: The results reveal important focal points for individual prevention measures. The targeted use of aids, an adapted environment, and supportive guidance in high-risk situations appears particularly effective.